2014
DOI: 10.1111/acem.12391
|View full text |Cite|
|
Sign up to set email alerts
|

Delaying the American Board of Emergency Medicine Qualifying Examination Is Associated With Poorer Performance

Abstract: Objectives: The initial step in certification by the American Board of Emergency Medicine (ABEM) requires passing a multiple-choice-question qualifying examination. The qualifying examination is typically taken in the first year after residency training. This study was undertaken to determine if a delay in taking the qualifying examination is associated with poorer performance. The authors also examined the relationship between in-training examination scores and qualifying examination scores.Methods: This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Although there has been only one study specific to laboratory science, numerous studies have been published that showed correlation between medical residency in-training preparation exams and pass rates of corresponding written board qualifying exams. [6][7][8][9][10][11] One study evaluated the American Board of Emergency Medicine in-training and qualifying examinations and found a significant correlation between in-training exams taken during the final year of residency and qualifying exam scores. 7 For each point increase above the mean on the in-training exam, a 0.6 point increase was observed on the qualifying exam.…”
Section: In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there has been only one study specific to laboratory science, numerous studies have been published that showed correlation between medical residency in-training preparation exams and pass rates of corresponding written board qualifying exams. [6][7][8][9][10][11] One study evaluated the American Board of Emergency Medicine in-training and qualifying examinations and found a significant correlation between in-training exams taken during the final year of residency and qualifying exam scores. 7 For each point increase above the mean on the in-training exam, a 0.6 point increase was observed on the qualifying exam.…”
Section: In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
“…[6][7][8][9][10][11] One study evaluated the American Board of Emergency Medicine in-training and qualifying examinations and found a significant correlation between in-training exams taken during the final year of residency and qualifying exam scores. 7 For each point increase above the mean on the in-training exam, a 0.6 point increase was observed on the qualifying exam. Another study compared senior pathology residents' in-training exam scores to the American Board of Pathology certification exam and showed increased pass rates for each quartile group on the in-training exam.…”
Section: In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
See 2 more Smart Citations
“…The ABEM QE is a 305 single-best-answer, multiple-choice question examination designed to measure medical knowledge recall (approximately 33% of all items) and clinical synthesis and diagnostic reasoning (approximately 66% of all items). 19,20 Between 10% and 15% of items include pictorial stimuli. The ABEM QE is a criterion-referenced examination; it does not use a performance curve or quota for passing or failing scores.…”
mentioning
confidence: 99%